Survei Tingkat Skill Related Fitness Pada Siswa – Siswi Sekolah Dasar Negeri Fase C Gugus 5 – 8 di Kecamatan Kedungkandang Kota Malang - Al Ashduqi, Ulin Najah; Wiguno, Lokananta Teguh Hari (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This research aims to find out how the level of physical fitness related to skills in students at State Elementary Schools in Gugus 5 - 8 in Kedungkandang District, Malang City, because there is no data related to students' physical fitness. Descriptive quantitative with random sampling technique is the method used in this study. The overall subjects taken in this study amounted to 95 students using the Indonesian Student Fitness Test (TKSI) instrument in data collection. Because based on the results of observations and initial interviews with PJOK teachers, the results obtained that physical fitness learning in grades 5 and 6 is carried out once a week, besides that PJOK teachers have never conducted physical fitness tests in accordance with TKSI. Thus, the results of this study indicate that the fitness status related to the skills of students at the State Elementary School of Gugus 5 - 8 phase C in Kedungkandang District, Malang City with a percentage of 56.42% which is included in the moderate category. In the Excellent category there are 0 frequencies, in the Good category there are 3.37% or 4 frequencies, in the Moderate category there are 44.21% or 70 frequencies, in the Lack category there are 8.84% or 21 frequencies, and in the Very Lack category there are 0 frequencies.